Cryptic species in an ancient flowering‐plant lineage (Hydatellaceae, Nymphaeales) revealed by molecular and micromorphological data. Issue 1 (14th April 2019) - Sokoloff, Dmitry D.; Marques, Isabel; Macfarlane, Terry D.; Remizowa, Margarita V.; Lam, Vivienne K.Y.; Pellicer, Jaume; Hidalgo, Oriane; Rudall, Paula J.; Graham, Sean W.
Abstract : The flora of the southwestern Australian biodiversity hotspot is rich in endemic species, many of which remain to be discovered or properly described; estimates of species diversity and levels of endemism should take into account the possible occurrence of cryptic species. Here we explore taxonomic diversity in a Western Australian lineage belonging to the primarily Australian genus Trithuria, the sole genus of Hydatellaceae (Nymphaeales). Recent molecular evidence supports the existence of cryptic species in self‐pollinating members of section Trithuria . We investigate Western Australian plants currently classified as T. australis s.l., a self‐pollinating member of the section Hydatella . Using evidence from microsatellite data (SSRs), an expanded molecular phylogenetic analysis based on four plastid markers, and fruit micromorphology, we suggest that material traditionally classified as T. australis s.l. belongs to at least four species. Two species occur in the northern part of the distribution range of the group (31° S to 33°27′ S), and two in the southern part (33°27′ S to 35° S). Each northern species has distinctive fruit micromorphology not recorded in other members of the genus. The two southern species are well characterized by molecular characters and seem to be allopatric, but lack obvious morphological differences from each other. We describe one of the northern species as T. fitzgeraldii sp. nov. However, clarifying the names of the other three species is currently problematic as T. australis and another available name are based on collections made 117 years ago, from localities distant from any subsequent records of Hydatellaceae. Based on genome size estimations, we also demonstrate two ploidy levels in the T. australis complex. Our study supports the view that species diversity in Hydatellaceae is strongly underestimated.